El Excentrico, 1967-02-05 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
February 05, 1967 [5 de enero de 1967]. No volume or issue number. Cover has group portraits of six attendees of the San Jose Sweetheart Ball. The headline reads, "American GI Forum - San Jose Sweetheart Ball - Saturday Feb-18th 07:30 PM Little New Yorker 1400 Martin Ave. Santa Clara."